Readings from the first century world primary sources for New Tesdtament study - Elwell, Walter A.; Yarbrough, Robert W. (Grand Rapids, MI Baker, 1998)
Includes bibliographical references and indexes.
Keywords: Church history -- primitive and early church, ca. 30-600 -- sources; Bible -- quotations